Use of virtual reality in physical rehabilitation: A narrative review - Swati Bhise; Manisha Rathi; Rachana Dabadghav; Janhavi Atre (Current Medicine Research and Practice, 2024)
Virtual reality (VR) has emerged as an innovative technology in various fields. It transforms how we experience and interact with the world, and it has also developed into physical rehabilitation. Rehabilitation has also evolved from mere exercises to using technology while giving exercises to patients. VR is a technology that can enhance treatment and improve outcomes. VR uses computer-generated three-dimensional interactive simulation models, allowing users to engage in environments resembling real-world objects and events. An extensive literature search was conducted on SCOPUS, PubMed, the Web of Science and relevant rehabilitation databases. The keywords ‘virtual reality’, ‘rehabilitation’ and ‘physical therapy’ were employed to identify pertinent studies. The inclusion criteria encompassed research investigating the use of VR in rehabilitating musculoskeletal, neurological and cardiovascular conditions. VR has been used in various rehabilitation domains. It is effectively used in balance and gait training, cognition and memory training, pain management, muscle strengthening, etc. It has also been shown to improve adherence to exercises. VR training in physical therapy represents a transformative advancement in rehabilitation. Integrating VR technology offers many benefits, including enhanced engagement, customised therapy regimens and a safe environment for patients to practice and improve their physical abilities. The evidence from various studies indicates its potential to improve outcomes for individuals with a wide range of physical impairments.